Artéria radial na ampliação do uso de enxertos arteriais para revascularização do miocárdio: considerações anatômicas e tática cirúrgica - Dallan, Luís Alberto (1996)
The aim of our study is to determine the microscopical anatomy imunohistochemistry and electronical scanning analysis of the radial artery (RA); 269 patients underwent myocardial revascularization with a RA graft were studied, performing 319 RA anatomoses; 80.7% patients were male and 93.7% Caucasians. The left internal thoracic artery (LITA) was used in 246 patients at the present surgery and 17 LITA were used before (redo-operation), performing 97.8%. LITA conduits employed altogether. The patients received another additional conduits: 59 (21.9%) right internal thoracic arteries (RITA); 17 (6.3%) right gastroepiploic arteries (RGEA); 161 (59.8%) saphenous vein grafts. An average of 3.4 anastomoses/patient were constructed. There was no post-operative complications such as ischemia or infection envolving the hand with interruption of the RA supply. The RA immunohistochemistry and electronical scanning microscopy showed that the internal elastic layer is developed and the media layer presented muscular fibers sheafs surrounded by collagen fibers more than elastic fibers. The post-operative complications include respiratory distress (21 -7.8%), atrial fibrillation (21 -7.8%), and enzymatic or electrocardiographic signs (12-4.5%) of acute myocardial infarction. Six (2.2%) patients needed mechanical support with intraortic balloon pump. Early angiographic controls have been performed in 21 patients. One patient developed RA dissection during the angiographic study; in all other patients the RA patency was 100%. The overall in-hospital mortality rate was 2.2% (6 patients). Recently, different arrangements of the arterial grafts were adopted to achieve a more complete myocardial revascularization. The RA are frequently employed to sequential anastomosis with the inferior and lateral left ventricular coronaries. The RA proximal anastomosis is often performed with the LITA. Both the RGEA and the RITA are used as complementar arterial grafts. From 64 patients submitted to myocardial revascularization with RA last 3 months, 2 arterial conduits were performed in 62 (96.9%) patients, 3 arterial conduits were performed in 27 (42.2%) patients and 4 or 5 arterial conduits were performed in 8 (12.5%). Although the pedicled internal thoracic artery graft remains the primary arterial conduit for myocardial revascularization, the radial artery is an excellent additional bypass conduit.